An evaluation of the eutrophication prevention potential of high rate Algae Ponds through the development of a deterministic design model - Van der Merwe, Izak Schalk Willem (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stellenbosch University, 2016.